Nitrous oxide dynamics in the Kara Sea, Arctic Ocean - Muller, Sofia; Fripiat, François; Jaccard, Samuel L.; Ponsoni, Leandro; Hölemann, Jens A.; Martínez-García, Alfredo; Delille, Bruno (Frontiers in Marine Science, 2024)
Previous studies have reported an accumulation of nitrous oxide (N2O) on shallow continental shelves of the western Arctic Ocean. In this study, we sampled seawater profiles for N2O measurements in the eastern Arctic shelves, in the North Kara Sea, in the context of the Arctic Century Expedition. Despite some variability in the vertical distribution, we typically observe an accumulation of N2O in shelf bottom waters, which correlates with a fixed nitrogen (N) deficit. Longer residence times on the shelf promote greater N2O enrichment and a larger fixed N deficit. These observations point towards N2O production at depth, linked to benthic denitrification processes that are intensified on productive shelve areas. However, in surface waters, physical processes – i.e. temperature-dependent solubility and air-sea exchange – emerge as the main factor controlling N2O concentrations. We observe low saturations of 80% at the surface of open ocean stations influenced by water that has previously flowed beneath sea ice. Arctic surface water becomes undersaturated due to cooling and remains undersaturated due to limited air-sea exchange. River supply does not exert a discernable influence on N2O concentrations of the studied area. This study reveals the potential of the Arctic Siberian shelves as a sink of atmospheric N2O during the summer.